Macroeconomic Modeling of the Russian Economy under Uncertainty - VAFIN, LENAR R.; SAFIN, RINAT I. (The journal of contemporary issues in business and government, 2021)
Within the framework of this article, macroeconomic modeling of the Russian economy is carried out under conditions of uncertainty. The spread of the new coronavirus infection and the introduction of appropriate protective restrictive measures, as expected, led to a recession in the world economy and the economy of Russia. If earlier the determining factor of Russia’s economic growth was the conjuncture of the world fuel and energy market, now, in the current restrictive conditions, the problem of changing the development paradigm has become especially acute. This fact and other conditions that form a single system of interconnected factors are reflected in the developed structural econometric model of the Russian Federation. By combining possible options for changing the exogenous factors of the model under consideration based on the scenarios proposed by the Ministry of Economic Development of the Russian Federation (MED of the Russian Federation), a medium-term scenario forecast of the main socio-economic factors until 2023 was made.